2018
DOI: 10.1002/elan.201800125
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Decorated Graphene as a High Performance Sensor for Determination of Trace Hydrazine Levels in Water

Abstract: Electrochemical sensors provide a selective, sensitive and an easy approach to detect hazardous substances such as hydrazine. Herein, we investigate a facile route for the fabrication of a nanostructured composite based on Au nanoparticles (AuNPs) decorated graphene and present its sensing performance towards hydrazine. Our strategy involves electrophoretic deposition (EPD) of graphene oxide (GO) on Au substrate to obtain a uniform layer EPD‐GO, followed by electrochemical reduction of GO to yield high quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 61 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…The results showed that there is no statistical difference in obtained hydrazine concentration values from different real samples. Our results are satisfactory and match the recovery values of hydrazine sensors previously reported in the literature [46,47], evidencing that the proposed printed sensor is a good candidate for the determination of hydrazine in real water samples.…”
Section: Real Sample Analysissupporting
confidence: 89%
“…The results showed that there is no statistical difference in obtained hydrazine concentration values from different real samples. Our results are satisfactory and match the recovery values of hydrazine sensors previously reported in the literature [46,47], evidencing that the proposed printed sensor is a good candidate for the determination of hydrazine in real water samples.…”
Section: Real Sample Analysissupporting
confidence: 89%
“…The surface morphologies of the various modified electrodes were characterized by SEM and EDX ( Figure 1 ). Compared with the surface of the GO/GCE ( Figure 1 A), SH-GO/GCE ( Figure 1 B) surface showed more folds [ 37 ], and these large specific surface areas provide a larger adhesion area for the loading of metal nanoparticles. At the same time, it is also beneficial to the complete contact between electrolyte and electrode surface [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, electrochemical sensors offer an efficient, easy-to-use, sensitive, and simple approach to detecting an analyte of interest in the liquid phase. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electrochemical sensors offer an efficient, easy-to-use, sensitive, and simple approach to detecting an analyte of interest in the liquid phase. 14,15 Some nanomaterial-modied electrodes have been reported for the quantication of acetone. For instance, metal oxides, such as TiO 2 , SnO 2 , Co 3 O 4 , Ag 2 O, W 18 O 49 , ZnO, and WO 3 , due to their intrinsic catalytic behavior and tunable size and shapes, have been extensively used for the development of acetone sensors.…”
Section: Introductionmentioning
confidence: 99%